2015
DOI: 10.1371/journal.pone.0123140
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Locally Established Reference Intervals for Hematology and Biochemistry Parameters in Western Kenya

Abstract: BackgroundImportant differences have been demonstrated in laboratory parameters from healthy persons in different geographical regions and populations, mostly driven by a combination of genetic, demographic, nutritional, and environmental factors. Despite this, European and North American derived laboratory reference intervals are used in African countries for patient management, clinical trial eligibility, and toxicity determination; which can result in misclassification of healthy persons as having laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
45
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 19 publications
18
45
1
1
Order By: Relevance
“…Compared to males, females had significantly higher WBC, neutrophil, and lymphocyte counts than males. This result is in agreement with the West Kenyan 23 report which showed as there were significant differences in WBC, neutrophil, and lymphocyte counts between male and female adolescents 23 .…”
Section: Discussionsupporting
confidence: 93%
“…Compared to males, females had significantly higher WBC, neutrophil, and lymphocyte counts than males. This result is in agreement with the West Kenyan 23 report which showed as there were significant differences in WBC, neutrophil, and lymphocyte counts between male and female adolescents 23 .…”
Section: Discussionsupporting
confidence: 93%
“…Firstly, many studies in the African setting have reported significantly lower hematologic parameters compared to values obtained from Caucasians [1216, 27]. Secondly, within the US setting, lower values have been observed for participants of African descent [23].…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out in Kenya to establish reference intervals for hematology parameters in the local population, the authors found differences compared with other regions, highlighting the importance of defining normal reference values, such as for eosinophilia, for populations in Africa. 54 Several previous studies and health guidelines for imported diseases in immigrants use absolute eosinophilia as single indicator of helminth infection. Taking into account our results, relative eosinophilia and hyper-IgE should be considered as better indicators of the presence of helminths in sub-Saharan immigrants.…”
Section: Discussionmentioning
confidence: 99%